(untitled) (Pädagogische Horizonte, 2018)
We report on a new technical way on conjecturing and proving elementary geometry statements. This new method relies on some Automated Reasoning Tools, embedded in the dynamic geometry software tool GeoGebra, and it may support inquiry learning at various levels. We provide examples of mathematical inquiries that may be better approached by the students by using our method during the exploration process.